2018
DOI: 10.4274/meandros.02411
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Perceived Pain During the First Week of Rapid Maxillary Expansion Treatment

Abstract: Objective:The aims of this study were to investigate the time at which pain started, the duration and intensity of the pain, the teeth affected in the mouth and whether sex was important in the perception of pain during the first week of rapid maxillary expansion (RME) treatment. MaterialsandMethods:Sixty-two patients, 30 boys (mean age 12.91±0.70 years), 32 girls (mean age 13.16±0.52) undergoing RME treatment with an acrylic-bonded appliance was surveyed. The appliance was activated with two turns per day. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…[7] e studies have revealed that gender is not a significant factor in reporting pain. [26,27] e present study's data show that boys had significantly higher rates of pain than girls in 2 nd week. According to Campos et al, [28] the level of pain differed significantly by gender.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…[7] e studies have revealed that gender is not a significant factor in reporting pain. [26,27] e present study's data show that boys had significantly higher rates of pain than girls in 2 nd week. According to Campos et al, [28] the level of pain differed significantly by gender.…”
Section: Discussionmentioning
confidence: 45%
“…It has been reported that the majority of RME patients experience pain, particularly during the early stages of expansion. [26] Here, we observed that the highest level of pain was detected during the 1 st week of expansion and gradually decreased over time.…”
Section: Discussionmentioning
confidence: 61%
“…Regarding study design, five studies were randomized clinical trials [ 2 , 12 , 15 , 16 , 17 ], one was a prospective study [ 3 ], one was a parallel cohort study [ 1 ], and one was divided into two phases, the first of which was a randomized, controlled clinical trial and the second of which was a prospective case series (The authors decided to include the second part of this study in the review too because, although it was defined as a prospective case series, a statistical analysis of the data was still performed) [ 9 ]. For two studies, the study design was not clearly defined by the authors [ 5 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rapid maxillary expansion (RME) is an orthodontic–orthopedic treatment routinely performed worldwide in growing subjects with transversal deficiency of the maxillary arch, with or without a crossbite [ 1 , 2 , 3 , 4 ]. This treatment can be performed in primary, mixed, or permanent dentition [ 1 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation